Therapeutic Challenges for Cisplatin-Resistant Ovarian Germ Cell Tumors - De Giorgi, Ugo (Cancers (Basel), 2019)
The majority of patients with advanced ovarian germ cell cancer are treated by cisplatin-based chemotherapy. Despite adequate first-line treatment, nearly one third of patients relapse and almost half develop cisplatin-resistant disease, which is often fatal. The treatment of cisplatin-resistant disease is challenging and prognosis remains poor. There are limited data on the efficacy of specific chemotherapeutic regimens, high-dose chemotherapy with autologous progenitor cell support and targeted therapies. The inclusion of patients in clinical trials is strongly recommended, especially in clinical trials on the most frequent male germ cell tumors, to offer wider therapeutic opportunities. Here, we provide an overview of current and potential new treatment options including combination chemotherapy, high-dose chemotherapy and molecular targeted therapies, for patients with cisplatin-resistant ovarian germ cell tumors.